OP37 Can Local Ultra-Orphan Patient Evidence Shape Global Understanding?. (2017) - Livingstone, Heidi; Upadhyaya, Sheela; Thomas, Lizzie; Leng, Gillian
Abstract : INTRODUCTION: Written patient evidence is submitted to the National Institute for Health and Care Excellence (NICE) by patient organizations and their nominated patient experts. We reviewed the impact that patient evidence had on the committee's decision making. This local learning can help generate global opportunities for Health Technology Assessment (HTA) bodies and patient groups to further develop their understanding and methodology about how patient evidence can support HTA decision making for ultra-orphan conditions. METHODS: There were two phases. Phase one was an online questionnaire about the impact of patient evidence on the committee's decision making for ultra-orphan HTA evaluations. It was sent to the committee chair, lay committee members and selected other committee members. Phase 2 developed the initial questionnaire findings using in-depth interviews with the committee chair and the lay members. These gained further understanding of the impact of patient evidence and the themes raised. RESULTS: Key findings showed patient evidence was helpful to understand the: Burden of disease Patient population Likely uptake of new medicines Impact on carers. For ultra-orphan conditions, where other forms of evidence are scarcer, patient evidence is fundamental to understanding patient needs, the impact of the disease, patient population and preferences. CONCLUSIONS: Patient evidence was useful for the committee in different ways; it provided the committee with new evidence and it helped the committee understand and interpret the evidence submitted by others. Both are key to committee decision making. It was clear that due to the very small patient population, patient groups knew the patient population, their stage of disease, and their preferences in detail. The findings will be used to inform an updated patient submission template for ultra-orphan HTAs, and supporting guide. These will be available on the NICE website and offered to the HTAi Interest Group on Patient and Citizen Involvement so they can be shared globally.